1977
DOI: 10.1136/gut.18.5.343
|View full text |Cite
|
Sign up to set email alerts
|

Giardiasis: clinical and therapeutic aspects.

Abstract: SUMMARY Malabsorption was present in 29 of 40 symptomatic patients with giardiasis. Twentythree had impaired D-xylose absorption; in 20 vitamin B12 absorption was low, and 15 patients had steatorrhoea. More severe malabsorption was associated with more marked histological abnormalities. Metronidazole, 2-0 g as a single daily dose on three successive days, produced a parasitological cure rate of 91%. In contrast, the standard course of mepacrine, 100 mg thrice daily for 10 days, eradicated the parasite in only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(36 citation statements)
references
References 31 publications
2
32
0
1
Order By: Relevance
“…On the other hand, Brandborg et al found normal jejunal histology with absence of inflammatory cells in symptomatic patients (with diarrhea) (29). A higher incidence of giardiasis has been reported in hypogammaglobulinemic patients (200); it appears that more severe damage to the villus is present in the hypogammaglobulinemic patients than in those with a normal immune system (65). Interestingly, the degree of villus pathology observed in patients with AIDS is comparable to that in immunocompetent patients (103), although AIDS patients are deficient in CD4 ϩ T cells.…”
Section: Giardiasismentioning
confidence: 99%
“…On the other hand, Brandborg et al found normal jejunal histology with absence of inflammatory cells in symptomatic patients (with diarrhea) (29). A higher incidence of giardiasis has been reported in hypogammaglobulinemic patients (200); it appears that more severe damage to the villus is present in the hypogammaglobulinemic patients than in those with a normal immune system (65). Interestingly, the degree of villus pathology observed in patients with AIDS is comparable to that in immunocompetent patients (103), although AIDS patients are deficient in CD4 ϩ T cells.…”
Section: Giardiasismentioning
confidence: 99%
“…Various clinical and epidemiological studies [1][2][3][4] suggest the importance of Giardia lamblia infection on childhood morbidity related to diarrheal disease. Understanding the natural history of Giardia infection is complicated by considerable variations in cyst excretion.…”
Section: Introductionmentioning
confidence: 99%
“…A transmissão pode ocorrer através da ingestão de cistos maduros em água sem tratamento adequado, alimentos contaminados por insetos e partículas de dejetos fecais em suspensão no ar ou de indivíduo para indivíduo em locais com aglomeração de pessoas (SANTANA et al, 2014). A infecção pode permanecer assintomática, ou apresentar sintomas como diarreia, dor abdominal, gases, vômito, perda de peso, má absorção de nutrientes e gorduras como, vitaminas A, D, E, K, vitamina B12, ferro, xilose e lactose e consequentemente a desnutrição (NETO et al, 2008;REY, 2001;WRIGHT;TOMKINS;RIDLEY, 1977).…”
Section: Discussionunclassified